(untitled) (Research, Society and Development, 2021)
Introduction: The World Health Organization in 2020 declared the SARS-CoV-2 pandemic, which has high transmissibility causing a fatal acute respiratory syndrome. Furthermore, a rare and deadly disease, in addition to the above mentioned, proven by a virus is Ebola in primates (including man), which constitutes the most deadly and disseminated disease in global outbreaks. Objective: to establish a comparison between coronavirus and Ebola with a focus on mortality and lethality. Methodology: an integrative literature review using online databases such as: BVS, SCIELO, PUBMED, MEDLINE, WHO, IDRC, MS, CDC. Results and Discussions: In 2020, the 10th Ebola outbreak occurred and the 2nd largest since its discovery in 1976, 3,470 cases were reported. Currently, in 2021, according to Epidemiological Week (SE) 43, on October 30, 246,407,251 cases of COVID-19 have been confirmed in the world. Comparing the coronavirus, which has a fatality rate of 6.1% of infected people, with the threat of the Ebola virus, covering 90%, it is considered more aggravating, as it quickly causes the deaths of the sick. Conclusion: Thus, COVID-19 and Ebola are viruses that threaten global public health, due to their high rates of morbidity and mortality. However, it is necessary to follow the protocols and recommendations of the World Health Organization in the control and prevention of diseases.